2009
DOI: 10.1103/physrevb.79.075422
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of CO adsorption on flat, stepped, and kinked Au surfaces using density functional theory

Abstract: Our ab initio calculations of CO adsorption energies on low miller index (111), (100), stepped (211), and kinked (532) gold surfaces show a strong dependence on local coordination with a reduction in Au atom coordination leading to higher binding energies. We find trends in adsorption energies to be similar to those reported in experiments and calculations for other metal surfaces. The (532) surface provides insights into these trends because of the availability of a large number of kink sites which naturally … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 43 publications
(73 reference statements)
9
44
0
Order By: Relevance
“…In this sense, Meier et al 21 reported that for a Au (110) surface, for temperatures above 250 K, the adsorption of CO is discarded for by means of infrared reflection absorption spectroscopy data at pressures in the mbar range. These results agree very well with the absence of adsorbed CO on Au(332) observed from HRCL spectra of Figure 1b The role of under-coordinated atoms in the adsorptive properties of Au surfaces has been discussed by Mehmood et al 20 and the calculated energy of adsorption of CO on flat, stepped and kinked Au reveals a stronger adsorption on under-coordinated atoms; although, the energies of adsorption obtained are considerably smaller than for Pt surfaces. Weststrate 12 and Ruggiero 13 obtained the same conclusion using vicinal surfaces as substrates and techniques such as high resolution XPS, TPD and FTIR spectroscopy.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In this sense, Meier et al 21 reported that for a Au (110) surface, for temperatures above 250 K, the adsorption of CO is discarded for by means of infrared reflection absorption spectroscopy data at pressures in the mbar range. These results agree very well with the absence of adsorbed CO on Au(332) observed from HRCL spectra of Figure 1b The role of under-coordinated atoms in the adsorptive properties of Au surfaces has been discussed by Mehmood et al 20 and the calculated energy of adsorption of CO on flat, stepped and kinked Au reveals a stronger adsorption on under-coordinated atoms; although, the energies of adsorption obtained are considerably smaller than for Pt surfaces. Weststrate 12 and Ruggiero 13 obtained the same conclusion using vicinal surfaces as substrates and techniques such as high resolution XPS, TPD and FTIR spectroscopy.…”
Section: Resultssupporting
confidence: 87%
“…The adsorption of CO on bare Au single crystals of low Miller index such as (111), (100) and (110) has been explored in the past by various authors [20][21][22] . Even though these results were obtained by adsorbing CO at low temperatures, they provide an interesting framework to understand the reactiveness of Au surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Our DFT calculations showed that the on-top adsorption energies for Au(111), Au(100), Au(711), and Au(321) surfaces are À0.22 eV, À0.47 eV, À0.64 eV and À0.79 eV, respectively, corresponding to the coordinate numbers of nine, eight, seven, and six, respectively. The preferential CO adsorption at the lower coordinated sites or the surface atoms with lower coordination numbers have been also examined by other theoretical work [30] and the experimental results. [31][32][33][34] Au(100)-hex surface…”
Section: Examination By Dft Calculations Co-au 2 Clustermentioning
confidence: 98%
“…Henry et al [49] performed ab initio calculations of CO adsorption energies on Au(111) (100), (211) and (532) gold surfaces (the latter is depicted in Figure 7). For (111) the lowest adsorption energy was found (27 kJmol -1 ) and the energy difference for CO on the various sites on this surface (top, bridge, fcc and hcp hollow ) is less than 1 kJmol -1 .…”
Section: Maksymovych and Yatesmentioning
confidence: 99%